Longan from Florida - Ahmad R. Rafie; Jonathan Crane; Carlos Balerdi; Steven A. Sargent (EDIS, 2007)
HS-1105, a 2-page illustrated fact sheet by A.R. Rafie, Jonathan Crane, Carlos Balerdi, and Steven Sargent, provides an overview of longan production in Florida, its description, supply calendar, how it is packed for shipment, postharvest and preparation. Published by the UF Department of Horticultural Sciences, July 2007.